Small-Molecule BET Inhibitors in Clinical and Preclinical Development and Their Therapeutic Potential - Yu, Lei; Wang, Zhen; Zhang, Zhang; Ren, Xiaomei; Lu, Xiaoyun; Ding, Ke (Current Topics in Medicinal Chemistry, 2015)
Lysine acetylation is a pivotal mechanism in chromatin processes and the regulation of gene transcription. The acetylated lysine residues of histones are exclusively recognized by bromodomains (BRDs) known as epigenetic reader. Proteins containing BRDs undergo a post-translational modification (PTM) with development of cellular signaling and disease biology. The bromo and extra-terminal (BET) proteins are the second subfamily, which play important roles in cellular proliferation, cell cycle progression and chromatin compaction. Recently, a variety of small molecules have been reported to interact with the BET family proteins and accelerate the validation of BET proteins as druggable targets for treatment of cancers, inflammation and related diseases. In this review, we will summarize the small-molecule inhibitors in clinical and preclinical studies of the BET family bromodomains and their medicinal implications.
Keywords: Selectivity